Attracting Millennials: Legitimacy management and bottom-up socialization processes within accounting firms. (September 2016) - Durocher, Sylvain; Bujaki, Merridee; Brouard, François
Abstract: The competition to attract trainee accountants is fierce among accounting firms. Millennials seemingly have expectations in terms of work experiences and work environments that arguably cannot be ignored by accounting firms. This paper draws on a legitimacy framework to examine legitimacy management strategies utilized by large Canadian accounting firms in website communications directed at future employees. Our results demonstrate accounting firms appear to devote considerable effort to manage their legitimacy in the eyes of prospective employees and apparently use website communications to depict a work environment largely in accordance with Millennials' system of values and beliefs. This suggests a bottom-up socialization process is taking place whereby accounting firms adapt the workplace in response to future employees' expectations. Interviews with partners, managers and human resource advisors working in accounting firms support the idea of a bottom-up process. We conclude a two-way socialization process exists, where the firms and the new employees are both instigators and targets of socialization, jointly influencing what it is to be an accountant today.